A novel combined treatment for plasminogen deficiency with lung involvement. Issue 1 (4th November 2019) - Kilinc, Ayse A.; Tarcin, Gurkan; Kurugoglu, Sebuh; Schuster, Volker; Cokugras, Haluk; Celkan, Tiraje
Abstract: Plasminogen deficiency is characterized by fibrin‐rich pseudomembrane formation on all mucosal surfaces, particularly the conjunctiva. Respiratory system involvement is common; fibrin often obstructs the upper or lower respiratory tract, causing death. Although many treatments have been applied, no definitive treatment (especially of the respiratory involvement) yet exists. Although excision of tracheobronchial tree membranes affords temporary improvement, this should be performed only for patients in severe respiratory distress; the procedure triggers fibrin redeposition. Here, we share our experience with an 8‐year‐old plasminogen‐deficient female with severe lung involvement; we successfully delivered local tissue plasminogen activator followed by nebulized fresh frozen plasma.